Use of bronchial blocker in emergent thoracotomy in presence of upper airway hemorrhage, and cervical spine fracture: a difficult decision - Almeida,Carlos (2018)
Abstract Female, 85 y.o., weighting 60 kg, multiple trauma patient. After an initial laparotomy, an emergent thoracotomy was performed using a bronchial blocker for lung isolation (initial active suction was applied). During surgery, bronchial cuff was deflated, causing a self-limited tracheal blood flooding. A second lung isolation was attempted but it was not as effective as initially. Probably, a lung collapse with the same bronchial blocker was impaired in the second attempt because of the obstruction of bronchial blocker lumen by intraoperative endobronchial hemorrhage. Bronchial blocker active suction may contribute to obtain or accelerate lung collapse, particularly in patients that do not tolerate ventilator disconnection technique or lung surgical compression. The use of bronchial blockers technology was a valuable alternative to double lumen tubes in this case of emergent thoracotomy in the context of a patient having thoracic, abdominal trauma, severe laceration of tongue and apophysis odontoid fracture associated to massive hemorrhage, despite several pitfalls that could compromise its use. The authors intend to discuss the advantages and disadvantages of bronchial blockers comparing to double-lumen tubes for lung isolation, and the risks of our approach, in this complex multitrauma case.